2018
DOI: 10.1186/s12887-018-1135-6
|View full text |Cite
|
Sign up to set email alerts
|

Parent perspectives on school food allergy policy

Abstract: BackgroundFood allergy affects up to 8% of children in the U.S. There is minimal research to date on food allergy policies that are currently in place in schools and the opinions of parents of children with food allergy on the effectiveness of or need for these policies.MethodsAn electronic survey was disseminated to parents of children with food allergy. Frequencies were calculated to describe respondent characteristics and responses. Chi-square tests were performed to examine associations between school and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
1
25
0
4
Order By: Relevance
“…This paper is the largest qualitative study to‐date to report school‐related food allergy management challenges among students and families. While the existing research has reported on disease management strategies, variation in policies in the school setting, and lack of preparedness of school staff to address food allergies, few studies describe the impact of school food allergy policies on affected students and families from their own perspectives . As our participants described, they largely carry the burden of food allergy management, especially when school policies are poorly articulated or underdeveloped.…”
Section: Discussionmentioning
confidence: 92%
“…This paper is the largest qualitative study to‐date to report school‐related food allergy management challenges among students and families. While the existing research has reported on disease management strategies, variation in policies in the school setting, and lack of preparedness of school staff to address food allergies, few studies describe the impact of school food allergy policies on affected students and families from their own perspectives . As our participants described, they largely carry the burden of food allergy management, especially when school policies are poorly articulated or underdeveloped.…”
Section: Discussionmentioning
confidence: 92%
“…Third, parents perceived unclear roles in terms of the responsibility among school staff. Parents of children with a food allergy reported that a diverse school staff carries epinephrine on field trips and after-school activities and travels with every group [ 38 ]. Parents experienced lack of teacher involvement [ 36 ] in managing diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Parents reported the occurrence of incorrect insulin administration [ 37 ]. Second, parents perceived a lack of confidence among teachers regarding emergency response procedures [ 7 , 9 , 33 ], lack of equipment such as a refrigerator to store glucagon [ 12 ], and limited availability of emergency medication [ 27 , 38 ]. Third, they perceived a limited allergen-free environment.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the acute onsite management of FA, the intramuscular injection of epinephrine is the first-line treatment for acute severe systemic reactions such as anaphylaxis. For children ≥15 kg who are diagnosed to food-induced anaphylaxis, self-injectable/auto-injectable epinephrine prescriptions are strongly recommended to ensure the proper management of future occurrences [1,3,5].…”
mentioning
confidence: 99%
“…Despite growing awareness and the availability of general guidelines, the optimal elimination of causative food and control/prevention of FA reactions by meal services is not practically easy [1,5]. The special aspect of school meal services, the government, and school requires policies and standardized protocols for the effective prevention and preparedness strategies for FA and food-induced anaphylaxis.…”
mentioning
confidence: 99%